Differential expression of the cancer associated antigens T (Thomsen-Friedenreich) and Tn to the skin in primary and metastatic carcinomas. Issue 8 (August 1998) - Kanitakis, J; al-Rifai, I; Faure, M; Claudy, A
Abstract : AIM: To study the immunohistochemical expression of the Thomsen-Friedenreich antigen (T) and its precursor, Tn, in the skin in various cancers. METHODS: T and Tn antigens were studied with monoclonal antibodies in 91 primary premalignant and malignant lesions, 13 cases of Paget's disease, and 26 carcinomas metastatic to the skin. The material had been collected over a 10 year period, formalin fixed, and paraffin embedded. Diagnoses had been made after examination of standard histological sections, supplemented when needed by appropriate immunohistochemical staining. RESULTS: 21% and 29% of the primary cutaneous premalignant and malignant epithelial tumours expressed the Tn and T antigens, respectively. By contrast, 81% of metastatic carcinomas to the skin were Tn positive, while only 23% of them expressed the T antigen. All cases of Paget's disease were Tn positive but only 15% of them expressed the T antigen. The 21 nonepithelial tumours (including melanomas) were as a rule unreactive. CONCLUSIONS: The accumulation of the precursor (Tn) antigen in tumours metastasising to the skin highlights the incomplete glycosylation of carbohydrate antigens occurring in these tumours. The predominant Tn versus T antigen expression appears to be a useful immunohistochemical feature which may aid in the differentiation of primary cutaneous carcinomas from metastatic tumours.